The Forgotten Step in Hand Hygiene: a look at hand drying practices in the VFSM survey - Lustriane, Cita; Fanaike, Ruki; Khairunnissa, Dewintha Syandi; Ramadona, Aditya Lia (BKM Public Health and Community Medicine, 2024)
Purspose: Handwashing is a cornerstone defense against the growing threat of antimicrobial resistance (AMR). This study investigates the level of knowledge regarding proper handwashing techniques, specifically among participants in the Village Food Safety Movement (VFSM) Program. Method: We conducted a Pre-Post Test Intervention survey across selected villages participating in the VFSM program within all 34 Indonesian provinces. The survey assessed knowledge of proper handwashing techniques and availability of adequate handwashing facilities. Results: The survey revealed a low percentage of correct responses regarding both proper handwashing techniques and the adequacy of handwashing facilities. Even after the intervention, the percentage of correct responses remained below 25%. This highlights a critical knowledge gap: proper handwashing includes thorough drying after washing hands. Conclusion: This study reveals a concerning lack of understanding about the complete handwashing process, potentially hindering efforts to prevent disease transmission and AMR in Indonesia. Future research should prioritize interventions that specifically address hand drying practices in addition to washing techniques. Policymakers and healthcare professionals should integrate hand drying education into their AMR control strategies.